Systematic review of the epidemiology of non-collision injuries occurring to older people during use of public buses in high income countries. Issue 3 (September 2015) - Kendrick, Denise; Drummond, Avril; Logan, Pip; Barnes, Jo; Worthington, Esme
Abstract Each year more than 6000 people are injured on public buses in the UK, approximately half of whom are aged 65 or over. This review synthesises the published literature on the epidemiology of non-collision injuries occurring in older people using public buses, to enable understanding of the size and nature of the problem of injuries, and to explore strategies for improving the safety of public transport for older people. We searched PubMed, Embase, CINAHL, web of science, and Transport Research International Documentation (TRID). Studies were included if they were cross-sectional, case-control or cohort Studies. Pairs of reviewers independently screened Studies for inclusion, assessed risk of bias, and extracted data. Ten studies were included in the review. Older people and women were found to be over-represented in non-collision injuries. Most injuries occurred during daytime hours and on weekdays. Injuries most commonly occurred whilst passengers were standing and either moving around the bus, boarding, or alighting, and whilst the bus was accelerating or decelerating. Bruising was the most common injury amongst emergency department attenders, although between 18% and 33% suffered more serious injuries such as fractures or dislocations. Many injuries to older public transport users are potentially preventable public transport needs to be safe and accessible, and to be perceived as such by older people to ensure independence in outdoor mobility.